Postcard from Adolf von Oechelhäuser to Georg Bredig, May 1923 - Oechelhäuser, Adolf von (1923)
Postcard from Adolf von Oechelhäuser (1852-1923) to Georg Bredig (1868-1944). Oechelhäuser was an art historian and preservationist. He was a rector at the Technical University of Karlsruhe from 1902-1903 and 1909-1910.
Keywords: Universität Karlsruhe; College teachers; Bredig, Georg, 1868-1944; Oechelhäuser, Adolf von, 1852-1923